The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00330-007-0631-0
|View full text |Cite
|
Sign up to set email alerts
|

CT colonography: optimisation, diagnostic performance and patient acceptability of reduced-laxative regimens using barium-based faecal tagging

Abstract: To establish the optimum barium-based reduced-laxative tagging regimen prior to CT colonography (CTC). Ninety-five subjects underwent reduced-laxative (13 g senna/18 g magnesium citrate) CTC prior to same-day colonoscopy and were randomised to one of four tagging regimens using 20 ml 40%w/v barium sulphate: regimen A: four doses, B: three doses, C: three doses plus 220 ml 2.1% barium sulphate, or D: three doses plus 15 ml diatriazoate megluamine. Patient experience was assessed immediately after CTC and 1 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
1
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 23 publications
2
85
1
2
Order By: Relevance
“…This is surprising, and other studies using this technique have produced poor results [17]. Most practitioners using barium tagging would combine it with at least a reduced dose of laxatives [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising, and other studies using this technique have produced poor results [17]. Most practitioners using barium tagging would combine it with at least a reduced dose of laxatives [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Most practitioners using barium tagging would combine it with at least a reduced dose of laxatives [13]. Taylor et al [3] reported a reduced laxative CTC regimen using bariumbased tagging. This was tolerated better than full laxative bowel preparation and produced results comparable to Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…These were modified from a previous study by Taylor et al [3]. Patients completed the questionnaires while they waited for their CT examination.…”
Section: Methodsmentioning
confidence: 99%
“…An interview topic guide was developed by three health psychology researchers, BLIND FOR REVIEW, following consultation with three radiologists (with experience of over 1000 CTC examinations each; BLIND FOR REVIEW) and literature review [7][8][9][10]14 . Open-ended questions were presented in a flexible order (see Table 1 for key questions).…”
Section: Methodsmentioning
confidence: 99%
“…However, many patients perceive laxative bowel preparation as the worst aspect of the test 4,5 and the addition of 'faecal tagging' may add additional burden. Quantitative studies of acceptability have found non-laxative preparation to be equivalent or superior to full-laxative preparation in terms of its acceptability [6][7][8][9][10] . However, although non-laxative CTC is likely to be better tolerated, its diagnostic accuracy compared to full-laxative studies is currently uncertain and so this preparation is generally reserved for patients considered unfit for full catharsis 11 .…”
Section: Introductionmentioning
confidence: 99%